Contamination of the local produced broilers carcasses with Escherichia coli O157:H7 and its effect in public health in Diyala province: Shukr M. Yaseen1; Ahmed M. Saleh2 and Rafid S.A.Al-Zubaidy3 - Al-Zubaidy, Rafid S.A. (The Iraqi Journal of Veterinary Medicine, 2018)
The study was conducted to indicate the contamination of the local produced broilers carcasses by Escherichia coli O157:H7, and its effects on public health. Sixty samples of local produced Broilers were collected randomly from five different areas in Baquba center of Diyala governorate, (Iraq). Thirty samples to each were collected in summer, from the beginning of July to end of August, and in winter season from the beginning of December to end of January to investigate their microbial load. All summer samples had significantly (P<0.05) higher microbial count of Coli-form Bacteria, Escherichia coli and E.coli O157:H7 than winter samples, but there were no significant differences in the mean values of Escherichia coli count CFU/g, and E.coli O157:H7 count between summer and winter seasons. The conclusion of study showed that the contamination of local produced broilers by these bacteria was higher through summer as compared to winter season; the reason is because of temperature in summer which leads to growth and Proliferation of these bacteria and misuse of preparation and production of meat acts to increase the microbial load in these products.